Learning Outcomes in Dribbling the Ball Through the STAD Learning Model: Elementary School Students' Football Game Material - Upa’, Andika Tandi; Sahabuddin, Sahabuddin; Mappaompo, M. Adam; Suwardi, Suwardi; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to improve student learning outcomes in dribbling skills in soccer games through the implementation of the Student Teams Achievement Divisions (STAD) cooperative learning model. This study used a classroom action research method with 24 fifth-grade students of Elim Christian Elementary School Makassar as research subjects. Data were collected through learning outcomes tests covering cognitive, affective, and psychomotor aspects. The research instruments were observation sheets, skills tests, and assessment rubrics. Data analysis was carried out descriptively and quantitatively by comparing learning outcomes in pre-cycle, cycle I, and cycle II conditions. The findings of the study are that all learning areas improved significantly. In pre-cycle conditions, the cognitive aspect averaged 58.75, the affective 62.08, and the psychomotor 55.42, with a 16.70% completion rate (4 out of 24 students). The average score increased to 72.92 for cognitive, 75.83 for affective, and 71.25 for psychomotor after STAD was implemented in cycle I, and the completion rate increased to 54.20%–62.50% (13–15 students). In cycle II, learning outcomes were ideal, with an average score of 84.58 for cognitive, 86.25 for emotional, and 83.75 for psychomotor, and a 100% completion rate (24 students). The average score increased 44.55% from pre-cycle to cycle II (58.75 to 84.86). Elim Makassar Christian Elementary School grade V pupils' dribbling skills have improved greatly with STAD cooperative learning. Students' conceptual knowledge, learning attitudes and motivation, and motor skills improved dramatically using this strategy. This study suggests using the STAD model to improve primary school physical education dribbling skills.